Pengembangan Model Pembelajaran Picture and Picture Terhadap Materi Gerak Lokomotor Siswa Kelas V SD - Epi Supriyani Siregar; Imanuddin Siregar; Dicky Edwar Daulay; Lady Rodearni Jawak (Departement of Mathematics Education, 2023)
This study aims to determine the development of a picture and picture learning model for locomotor motion material for fifth grade students at SD Negeri 060890. The research method used by researchers is the Research and Development method. Research and development (R&D) is a basic research activity to obtain information on user needs (needs assessment), then proceed with development activities to produce products and examine the effectiveness of these products (Sugiyono, 2014). Based on the table presented on the previous page, it can be seen that the total score achieved by the teacher in learning through locomotor motion using the picture and picture model with media images at meetings is 35 with Enough criteria. It can be seen in the table, at the meeting that the teacher's skills have not achieved success according to the indicators set. Therefore, at the next meeting the researcher must be able to carry out improvements in learning using poetry writing strategies using picture and picture models with picture media. An effective way for students to avoid pressure is by playing rock-paper-scissors or throwing the ball while singing the rabbit and when the ball stops, it comes forward to show pictures and imitate its movements. After that, the exploration stage. At this stage the teacher forms a discussion group to discuss locomotor movements based on the images shown. The teacher forms this group to make it interesting. In his creations, groups can be made with animal names. And the group imitated the movement based on the animal's name. Next, the teacher provides a learning evaluation. The teacher calls students one by one to imitate what the teacher shows in the picture. Finally, teachers and students reflect on learning. This activity is to get students' responses to the material that has been implemented.